INFRASTRUCTURE INVESTMENT POLICY TO BOOST ECONOMIC GROWTH AND INCREASE EMPLOYMENT - Gunawan Widjaja (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
In terms of the economic factors, it has been noted that infrastructure investment policy is considered as one of the strategies, which can be carried out to improve the economy and create job opportunities. Such an approach is performed in this research. Findings prove that appropriate infrastructure investment can leverage even higher growth inducing multiplier effects, boost productivity, and encourage growth of associated industries. Infrastructure sectors such as transport, energy, and telecommunications development would not only create jobs during the construction stage but would also create a further demand for employment within other support industries. Nevertheless, the success of this strategy will depend on the correct preparation, effective realization, and cooperation between public and private bodies. In summary, it is evident that an efficient and inclusive infrastructure investment strategy can be a crucial instrument of promoting economic development and job creation.